Decision support system classification and its application in manufacturing sector: A review - Hasan, Muhammad Syahid; Ebrahim, Zuhriah; Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam (Penerbit UTM Press, 2017)
The purpose of this paper is to review decision support system application trend in manufacturing sector. Following the introduction of decision support system, the paper has discussed the application of decision support system in manufacturing sector and identifies the trend in term of decision support system types and their application types. In year 2011 until 2015, the most preferred decision support system were developed by using the model application. It also been found that, most of the developed decision support system are used to support evaluation activities in manufacturing operations. This review provides research trend on decision support system for the recent five years (2011 -2015) in the context of decision support system application in manufacturing industry.